Impact of replacement of the central benzene ring in anthracene by a heterocyclic ring on electronic excitations and reorganization energies in anthratetrathiophene molecules. Issue 8 (14th April 2018) - Tripathi, Anuj; Prabhakar, Chetti
Abstract : The impact of changing the central benzene ring on the electronic excitations and reorganization energies ( λ ) of the anthratetrathiophene (ATT) molecules is studied by density functional theory (DFT) and time‐dependent DFT (TD‐DFT) quantum chemical calculations. The effect of changing the position of the sulfur atom at the periphery of anthracene on the optical and charge transfer properties is also studied. The calculated results suggest that the HOMO, LUMO, HOMO–LUMO energy gap, ionization potential (IP), electron affinity (EA), hole extraction potential (HEP), electron extraction potential (EEP), and reorganization energies ( λ ) are affected by replacing the central ring with different heterocyclic rings and the position of the sulfur atom. In addition, all molecules show good hole‐ and electron‐transport properties. This work may be helpful for future design and preparation of high‐performance charge‐transport materials. Abstract : * With change in position of Sulphur atom there is variation in charge transport properties.* Replacement of central six membered ring with five membered heterocyles results in blue shift.* Improvement in charge transfer properties with change in central ring.* HOMO‐LUMO gap increases with change in position of Sulphur atom at the periphery.* Study will be helpful for future design and preparation of high‐performance charge transport materials.